Uso e conservação de recursos botânicos por comunidades rurais do entorno ao Parque Nacional Serra de Itabaiana : uma abordagem etnobiológica - Lima, Juliano Silva (2010)
The units of preservation are important areas of ecological and social interest that aims protect for biodiversity and the sustenance from local communities. In Sergipe, one of the great importance areas for state biodiversity maintenance has been being PARNASI. Even with all that highlight, few are the developed jobs in this geared region to the aspects of partner-environmental involving the populations interaction of the spill with for local biodiversity. In this sense, that work consisted in a rising ethnobotanical aiming know the composition floristic and her respective utilities for the rural communities of the spill to PARNASI. This study is presented in three chapters. It in the first objectified accomplish a description of the study area and a theoretical and methodological rising of the jobs ethnobiological already published. In the second chapter objectified lift the wealth of arboreal species and shrub, from the popular knowledge, found in the four different forest fragments used by these communities. And in the third chapter was accomplished a rising ethnobotanical, identifying categories of popular uses for the vegetable resources, analyzing the importance of the arboreal species and shrub for the specialists of this region. That work was accomplished with four different rural communities of the spill to PARNASI, in the region defined by the river Poxim-Açú (Pedrinhas, Ladeira, Caroba e Cajueiro). The data were lifted, by means of the participating observation, interviews semi-structured, with 31 specialists recognized in the communities as detainers of the traditional knowledge. The inventory floristic with help of these specialists was at the same time done, in four atlantic forest indicated fragments from the communities' local utilization. The picked data enabled the elaboration of a listing contend 185 ethnospecies, grouped in 111 goods and 50 families. Regarding the origin that 83% of the species was observed are native of the region and just 17 % are exotic. The collection of the vegetable resources it's given in different Habitats being 67% collected in area of humid forest, 17% in boards areas and 16% in areas anthropogenic. The families with larger number of found useful species were Fabaceae (31ssp.), Myrtaceae (19ssp.) And Arecaceae (9ssp.). The species were classified in five use categories: Fuel (28%), mystic-farmcológico (21%), feed (18%), loggers (17%), other uses (16%). The general panorama of results of this work shows that there are use different from the flora standards among studied groups. The groupings accomplished by that study reflect that communities' way of life influences directly in the specialists' knowledge on the plants, differentiating it, even when they inhabit areas where the availability of the natural resources is similar.